PERFORMING RITE IN THE HOLI - Shankar Rao (Arts Academy)
The article is an in-depth study of the performing rite in the major festival of Holi celebration in marking communities with complex performances. This article deals with the complex performances of Holi among the Gor Banjara Lambani, a nomadic, pastoral community of Karnataka. It is a systematic descriptive analysis of the different stages of celebration as well as production of orature in the performance. It extensively deals with the Holi spring festival and analyzes the complexity of the rite of dhund as the celebration as a part of Holi. It investigates how time, space, and human bodies are its elements to create activities and events for the process of community life. The mythical significance of Holi in the performance and gender role in the Dhund rite are analyzed.